DOI: 10.14264/uql.2015.323
|View full text |Cite
|
Sign up to set email alerts
|

Respitatory virus infections during the first year of life a longitudinal community-based dynamic birth cohort study

Abstract: Background: Viral acute respiratory infections (ARIs) are the commonest illnesses experienced by all age groups, especially in infants where infection rates are highest. Nevertheless, during the molecular era, outside of hospital-based studies, little is known about the current aetiology and community burden of viral ARIs in infants and young children. The observational research in childhood infectious disease (ORChID) project is a prospective community-based birth-cohort study of healthy Australian infants an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 147 publications
(251 reference statements)
0
1
0
Order By: Relevance
“…3 Ct value >38, respiratory virus detection declined significantly (odds ratio 0.35, 95% CI: 0.27, 0.44 when ERV-3 was undetectable)(249). Thus, virus-negative swabs with an ERV-3 Ct value >38 were deemed to be of poor quality and removed from parts of the analysis, such as incidence calculations.Swab quality was monitored throughout the study and the number of ERV-3 negative specimens ranged from 19.6% to 44.6% in the first 8 months of the study(250).Analysis of ERV-3 positive and respiratory virus positive specimens showed that ERV-3 positive sample rates increased with age and varied by season(249), with ERV-3 positive rates in the first six months of age as a reference. Following a cluster of specimens that were negative for ERV-3, study nurses contacted parents and reminded them of the optimal swab technique they had been shown at enrolment.After this feedback, the number of ERV-3 specimens declined.Each swab was resuspended in 2mL of phosphate buffered saline from which 200µL was used for nucleic acid extraction.…”
mentioning
confidence: 99%
“…3 Ct value >38, respiratory virus detection declined significantly (odds ratio 0.35, 95% CI: 0.27, 0.44 when ERV-3 was undetectable)(249). Thus, virus-negative swabs with an ERV-3 Ct value >38 were deemed to be of poor quality and removed from parts of the analysis, such as incidence calculations.Swab quality was monitored throughout the study and the number of ERV-3 negative specimens ranged from 19.6% to 44.6% in the first 8 months of the study(250).Analysis of ERV-3 positive and respiratory virus positive specimens showed that ERV-3 positive sample rates increased with age and varied by season(249), with ERV-3 positive rates in the first six months of age as a reference. Following a cluster of specimens that were negative for ERV-3, study nurses contacted parents and reminded them of the optimal swab technique they had been shown at enrolment.After this feedback, the number of ERV-3 specimens declined.Each swab was resuspended in 2mL of phosphate buffered saline from which 200µL was used for nucleic acid extraction.…”
mentioning
confidence: 99%